2018
DOI: 10.1016/j.kint.2018.04.022
|View full text |Cite
|
Sign up to set email alerts
|

The AGES-Reykjavik Study suggests that change in kidney measures is associated with subclinical brain pathology in older community-dwelling persons

Abstract: Decreased glomerular filtration rate (GFR) and albuminuria may be accompanied by brain pathology. Here we investigated whether changes in these kidney measures are linked to development of new MRI-detected infarcts and microbleeds, and progression of white matter hyperintensity volume. The study included 2671 participants from the population-based AGES-Reykjavik Study (mean age 75, 58.7% women). GFR was estimated from serum creatinine, and albuminuria was assessed by urinary albumin-to-creatinine ratio. Brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Similarly, a high urinary albumin-to-creatinine ratio (UACR) was significantly associated with the presence of imaging markers of cerebral small vessel disease in middle-aged and elderly participants of the general population-based Rotterdam Study [ 10 ], and with an increase of the white matter hyperintensities (reflecting deteriorating cerebral white matter due to myelin breakdown) volume to the intracranial volume ratio in the Hisayama Study [ 11 ]. More recently, this association has been confirmed in the population-based AGES–Reykjavik Study (mean age 75 years), showing that participants with incident albuminuria (UACR >30 mg/g) had 21% more white matter hyperintensity volume progression compared with participants without incident albuminuria [ 12 ]. Recent studies, including a prospective Atherosclerosis Risk in Communities (ARIC) study [ 13 ], the Hisayama Study [ 14 ] and others, also found that increased albuminuria is consistently associated with the incidence of dementia.…”
Section: Association Of Increased Albuminuria With MCI and Dementiamentioning
confidence: 92%
“…Similarly, a high urinary albumin-to-creatinine ratio (UACR) was significantly associated with the presence of imaging markers of cerebral small vessel disease in middle-aged and elderly participants of the general population-based Rotterdam Study [ 10 ], and with an increase of the white matter hyperintensities (reflecting deteriorating cerebral white matter due to myelin breakdown) volume to the intracranial volume ratio in the Hisayama Study [ 11 ]. More recently, this association has been confirmed in the population-based AGES–Reykjavik Study (mean age 75 years), showing that participants with incident albuminuria (UACR >30 mg/g) had 21% more white matter hyperintensity volume progression compared with participants without incident albuminuria [ 12 ]. Recent studies, including a prospective Atherosclerosis Risk in Communities (ARIC) study [ 13 ], the Hisayama Study [ 14 ] and others, also found that increased albuminuria is consistently associated with the incidence of dementia.…”
Section: Association Of Increased Albuminuria With MCI and Dementiamentioning
confidence: 92%
“…Diabetes and hypertension are the most common risk factors universally, while obesity is an additional risk factor, especially in industrialized countries [ 272 , 273 , 274 , 275 , 276 , 277 , 278 , 279 ]. CKD is a cause of morbidity and mortality as it is an important predictor of end-stage kidney disease (ESKD), stroke and cardiovascular disease (CVD) [ 280 , 281 , 282 , 283 , 284 , 285 ]. CKD is characterized by albuminuria (a urinary albumin to creatinine ratio, uACR, above 30 μg/g) and/or a decrease of GFR to ≤60 mL/min/1.73 m 2 that persists for at least three months [ 48 , 49 , 50 ].…”
Section: Environmental Exposure To CD and Pb Toxic Kidney Burdenmentioning
confidence: 99%
“…The associations between [Cd] u , [NAG] u and [RBP] u were only seen in workers who had high levels of [Pb] b (≥21.9 μg/dL), corresponding to the 75th percentile or higher. In addition, the associations between [Cd] b , [NAG] u and [intestinal alkaline phosphatase] u only became statistically significant in workers who had [Pb] b ≥ 21.9 μg/dL [ 285 ]. This Cd–Pb interaction was seen although blood Pb in Belgian workers of 21.9 μg/dL was 6-fold higher than the 90th percentile blood Pb level of 3.66 μg/dL in a Korean study [ 300 ].…”
Section: Environmental Exposure To CD and Pb Toxic Kidney Burdenmentioning
confidence: 99%
“…31,36 This is not surprising given the common anatomic and vaso-regulatory features of the brain and the kidneys, lowresistant end organs that are susceptible to vascular damage, as both organs receive high-volume blood flow. 31 Individuals with proteinuria or reduced GFR are likely to have subclinical small vessel disease in the brain, [36][37][38] which is believed to play a causal role in cognitive impairment and dementia. 39 Another potential explanation would be shared risk factors between CKD and Figure 1.…”
Section: Discussionmentioning
confidence: 99%